Intersections Between Law and Artificial Intelligence - Krausová, Alžběta (International Journal of Computer (IJC), 2017)
The paper provides a concise overview of the interplay between law and artificial intelligence. Based on the analysis of legal resources, it identifies key topics, organizes them in a systematic manner and describes them in general, essentially regardless of specificities of individual jurisdictions. The paper depicts how artificial intelligence is applied in law, how law regulates artificial intelligence, and what are some theoretical legal questions that have been raised with regard to the developments in artificial intelligence.